A região e o mundo no romance Galileia de Ronaldo Correia de Brito - Borges, Queren Daniela (2022)
Ronaldo Correia de Brito is one of the most representative names of current Brazilian literature, author of several works, translated into different forms, such as theater, music and literature. His narratives dialogue with biblical texts, traditions and values, capturing anonymous speeches, of human types that populate a space and a time of the sertão turned into language. From the works of Ronaldo Correia is possible to visualize the representation of the sertões in contemporary times, of rural landscapes, of archaic origins, which point to another bias, with updated marks in a “complexly urban” sertões. In Galileia, 2008, the novel brings up the problem that involves literary regionalism at different levels. The sertão is seen under the imperative of modernity, but it still carries with it the marks of the past, of rural landscapes, of archaic origins. Thus, the present research proposes to discuss the possibilities that the work of Ronaldo Correia opens around the permanence or not of regionalism, since the globalized world is in the sertão, just as the sertão is everywhere where its disoriented characters pass. In this way, we seek to understand the power of this work, which associates the archaic hinterland and modernity, which creates new relationships between the local and the universal, and points from the vestiges of tradition to ways of saying the region in a new fictional diction. It is in this sense that we discuss, in this text, the aesthetic paths chosen by the author, analyzing the effects of traditions, intertextuality with passages from the Bible, manifestations of popular speeches and customs, the presence of the archaic world in the narrative, as ways to reinvent the sertão, which appears transfigured and saved from oblivion by the power of words and by the power of the refined plots of the language of fiction.